Steganography and its Application Prospects in Information Protection - Beridze, Besik; Donadze, Mikheil (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2025)
The paper discusses and characterizes computer steganography - as a creative and one of the promising components of information protection in the modern digital era. The paper describes the essence of steganography, provides its general characterization and presents the main concepts. The paper includes a detailed classification and analysis of computer steganography methods, including a comparison of digital steganography technologies LSB, DCT and Spread Spectrum. The practical part presents the software application "BSU_Stegano_v.1", which visually demonstrates the principles of steganographic methods. The paper aims to understand the perspectives of steganography, both in the context of legitimate uses and cybersecurity challenges, which contributes to improving data security practices.